Avion - Heberlandová, Katarína (Institute of ethnology and social athropology SAS, 2021)
The book is a unique combination of stories that its authors, Katarína Haberlandová and Ľubica Voľanská, have been collecting for several years. It is the story of the Avion apartment building (including the monument care related to this house under several political regimes, in terms of daily maintenance and, since 1985, monument protection). At the same time, it is the story of its inhabitants directly connected with the building and life in it. Last but not least, it is the story of the author of Avion's designs, the architect Josef Marek (1889-1966). In the stories, there is a visible interweaving of big and small histories, as all the stories mentioned above take place in a particular space and time, having in the background the history of Bratislava but also of the wider region or state formations of which the city and the place were a part of. The authors used two approaches - historical-architectural and art-historical; the other is ethnological/anthropological, based on the oral history method. This interdisciplinarity has helped create a book that is still unique in Slovakia, deepening the scientific knowledge in the fields of 20th-century architectural history and ethnology/social anthropology. At the same time, the book offers an engagingly grasped story to a broader public that would not usually reach for academic literature in these fields. Moreover, the way the book is written makes it possible to reflect the story of the house and its inhabitants, even for those readers who may not have had in-depth knowledge of it until now. Indeed, many aspects analysed through the authentic accounts of Avion's male and female residents are universal to our history. In different variations or shades, they took place not only in other apartment buildings in Bratislava but also influenced and moved the inhabitants' lives in other Slovakia cities. Finally, new impulses are emerging for the elaboration of research on the everyday life associated with the Avion apartment house, especially in the areas of the politics of memory and forgetting, the history of the politics of cooperative housing in Slovakia in the 20th century, the conservation of modern architectural heritage, as well as community-based ways of caring for housing in the present day. A significant role will continue to be played by linking Avion citizens' good and the not-so-good stories and memories.